Activity of Antibiotics and Potential Antibiofilm Agents against Biofilm-Producing Mycobacterium avium-intracellulare Complex Causing Chronic Pulmonary Infections - Elena Portell-Buj; Cecibel González-Criollo; Alexandre López-Gavín; Mariana Fernández-Pittol; Maria Antònia Busquets; Joan Estelrich; Montserrat Garrigó; Marc Rubio; Griselda Tudó; Julian Gonzalez-Martin (MDPI AG, 2022)
Nontuberculous mycobacteria (NTM) cause lung infections in patients with underlying pulmonary diseases (PD). The Mycobacteriumavium-intracellulare complex (MAC) is the most frequently involved NTM. The MAC-PD treatment is based on the administration of several antibiotics for long periods of time. Nonetheless, treatment outcomes remain very poor. Among the factors involved is the ability of MAC isolates to form biofilm. The aim of the study was to assess the in vitro activity of different antibiotics and potential antibiofilm agents (PAAs) against MAC biofilm. Four antibiotics and six PAAs, alone and/or in combination, were tested against planktonic forms of 11 MAC clinical isolates. Biofilm was produced after 4 weeks of incubation and analyzed with the crystal violet assay. The antibiotics and PAAs were tested by measuring the absorbance (minimum biofilm inhibition concentrations, MBICs) and by performing subcultures (minimum biofilm eradication concentrations, MBECs). The clarithromycin/amikacin and clarithromycin/ethambutol combinations were synergistic, decreasing the MBECs values compared to the individual antibiotics. The amikacin/moxifloxacin combination showed indifference. The MBIC values decreased significantly when PAAs were added to the antibiotic combinations. These results suggest that antibiotic combinations should be further studied to establish their antibiofilm activity. Moreover, PAAs could act against the biofilm matrix, facilitating the activity of antibiotics.